MODEL MANAJEMEN KNOWLEDGE SHARING BERBASIS PEMBELAJARAN INFORMAL: STUDI KUALITATIF DI PT PUSRI PALEMBANG - Darma Putra, Mgs. Prima; M. Ikhsan Assiddiq U.P., Masagus (Penerbit Lafadz Jaya, 2026)
This study aims to develop a knowledge sharing model based on informal learning within the PT Pusri Palembang factory environment, integrated into the 70:20:10 learning and development model. Using a descriptive qualitative approach, data were collected through participant observation, in-depth interviews, and document review. The study found that knowledge sharing practices at PT Pusri operate organically, driven by operational needs and generational differences between senior and junior employees. The knowledge sharing strategies implemented include CoP (Community of Practice), intergenerational mentoring, and a job rotation system. The study's primary finding is the formulation of